Secure IT systems : 21st Nordic Conference, NordSec 2016, Oulu, Finland, November 2-4, 2016. Proceedings /: 21st Nordic Conference, NordSec 2016, Oulu, Finland, November 2-4, 2016. Proceedings. (2016) - Unknown
No abstract available